JUSTIÇA RESTAURATIVA: UM ESTUDO EXPLORATÓRIO A PARTIR DA PERSPECTIVA DO PROFESSOR MEDIADOR ESCOLAR E COMUNITÁRIO - CARNEIRO, Alex Rodolfo (2017)
The present study approaches the implementation of the paradigm of restorative justice in the extent of the schools public inhabitants from São Paulo of the Management of Teaching of the area of São José dos Campos and he/she has as reference the Teacher's School and Community Mediator perspective. The objective consists of to investigate and to contemplate concerning the character of public politics of that movement, the way as PMEC understands that process starting from the own professional performance and in the way as it evaluates the receptivity of the school community to a model of confrontation of conflicts based on the dialogue and in the co-responsability in opposition to methods and punitive beginnings, traditionally employees in the school units. The research based on qualitative methodology by interviews half structured in categories a priori, by which the great level of personal adhesion was verified and of involvement of PMEC with the implementation of the paradigm of restorative justice and the distrust and the uncertainties with respect to the continuity of that public politics on the part of the state government and of the school community's support as a whole. At the end, it was reached the conclusion that, in fact, it governs the discontinuity movement and whithout characterization of that public politics. In compensation, that new model wins adhesion and solidity in the school context because of the performance and of PMEC and of her coherence with the autonomy beginnings and inherent citizenship.